2012
DOI: 10.1155/2012/356187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Competitive Flow on Hemodynamics in Coronary Surgery: Numerical Study of ITA-LAD Model

Abstract: Competitive flow from native coronary artery is considered as a major factor in the failure of the coronary artery bypass grafts. However, the physiological effects are not very clear. The aim is to research the impact of competitive flow caused by different left anterior descending (LAD) artery stenosis degrees on hemodynamics in internal thoracic artery (ITA) bypass graft. An idealized ITA-LAD model was built in CAD tools. The degree of the competitive flow was divided into five classes according to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In this case, both the graft and the target vessel contribute to the perfusion of the distal vascular bed in variable proportions depending on the hemodynamic condition that may induce vasodilation or vasoconstriction. Ding et al ( 23 ) analyzed the impact of competitive flow on wall shear stress and confirmed that graft flow is conditioned by native vessel flow. The amplitude of competitive flow is determined not only by the degree of stenosis of the target vessel but also by the volume of myocardial tissue perfused by the grafted artery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this case, both the graft and the target vessel contribute to the perfusion of the distal vascular bed in variable proportions depending on the hemodynamic condition that may induce vasodilation or vasoconstriction. Ding et al ( 23 ) analyzed the impact of competitive flow on wall shear stress and confirmed that graft flow is conditioned by native vessel flow. The amplitude of competitive flow is determined not only by the degree of stenosis of the target vessel but also by the volume of myocardial tissue perfused by the grafted artery.…”
Section: Discussionmentioning
confidence: 95%
“…These two aspects could explain the lack of a statistically significant difference between the target vessel degree of stenosis in the case of patent SVGs versus occluded SVGs. Ding et al ( 23 ) analyzed the impact of competitive flow on a computerized model of an ITA graft (4.6 mm diameter) anastomosed to the LAD (4.5 mm diameter) under an anastomosis angle of 45°. Simulations were performed for stenosis severities of 30%, 50%, 75%, and 100% and showed that the higher the degree of LAD stenosis was, the lower the mean velocity in the proximal LAD artery was with the opposite occurring for the ITA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clinical studies associating intermediate coronary stenoses with increased IMA graft failure, Shimizu et al[57] demonstrated that the shear stress of the in situ IMA is maintained despite the flow volume being reduced by flow competition. Ding et al[58] used computerized flow dynamic modeling to study competitive flow in an IMA-LAD graft model. In this study, they correlated the Time-Averaged WSS and the oscillatory shear index (OSI) with TVECA percent stenosis, and found that TAWSS dropped when the stenosis was < 75%; concomitantly, the OSI distribution increased below 75% stenosis, where high OSI predisposes to endothelial dysfunction and atherogenesis[59], while maintained WSS is responsible for normal endothelial function and endogenous vasodilator production such as nitric oxide (NO).…”
Section: Intraoperative Factors and Influencesmentioning
confidence: 99%
“…If myocardial ischemia is relieved by the combined IMA/TVECA flow, then TVECA WSS is normalized, and the IMA graft accommodates flow velocity and flow capacity according to its contribution to myocardial demand relief[66]. If the proximal stenosis in the TVECA is not functionally significant, such as described by Ding et al[58], then time-averaged WSS of the graft falls, and OSI increases, contributing to the development of a string sign configuration angiographically. This IMA conduit, under new conditions of ischemia, can physiologically respond accordingly to meet this perfusion demand deficit[64].…”
Section: Intraoperative Factors and Influencesmentioning
confidence: 99%
See 1 more Smart Citation